The Effect of Betel Leaf Water Decoction on Perineal Wound Healing among Post Partum Women - Nursupma Oktavia Darulis; Rini Kundaryanti; Shinta Novelia (Nursing and Health Sciences Journal (NHSJ), 2021)
The prevalence of maternity women with perineal injuries in Indonesia in the 25-30 year age group waa 24%, while the 32-39 year old was 62%. Perineal wounds are the cause of postpartum maternal bleeding. Postpartum causes are the main cause of 40% of maternal deaths in Indonesia. This study aimed to determine the effect of betel leaf water decoction on post partum women perineal wound healing at the Independent Practice of midwife R. Agustina in West Bandung in 2021. This research used the Quasi Experimental Design method, with the Post Only Control Group approach. The population in this study were all postpartum women who had grade I and II perineal injuries at PMB R. Agustina in July 2021 which consisted of 30 respondents. The location of this research was carried out at the Independent Practice of the midwife R. Agustina West Bandung in July 2021. The variables of this study were betel leaf boiled water and perineal wounds. The research instrument was the REEDA Scale. The results showed that the average perineal wound healing before intervention in the experimental group was 10.60 and after intervention was 5.87, while the average perineal wound healing before test was 10.87 and after the test was 6.93. There were differences in perineal wound healing between the experimental and control groups at PMB R. Agustina West Bandung (p-value = 0.012). This intervention is expected to be used by the community as a method in overcoming the problem of perineal wound healing among post partum women.